How the Gold Standard Functioned in Portugal: An Analysis of Some Macroeconomic Aspects - Duarte, António Portugal (2004)
The purpose of this study is to improve understanding of the gold standard period in Portugal through comparison with other monetary systems that were operated afterwards. Portugal was the first country in Europe to join Great Britain in the gold standard, in 1854, and it adhered to it for quite a long time. The principle of free gold convertibility of the Portuguese currency at a fixed price was abandoned in 1891, even though the classical gold standard as an international monetary system only began to fall apart as a result of the upheavals of the First World War. For the purposes of a macroeconomic study, we can thus first look at the expansion of the functioning of the gold standard in Portugal up to 1913. In addition to a desire to share the same monetary system as its trading and financial partner, the low price of gold and the domestic circulation of British gold coins also played a part, along with other factors, in the adoption of the gold standard in Portugal. While it was in force, it provided a nominal stable anchor and a mechanism of credible commitment, even though Portugal’s monetary authorities broke the “rules of the game”. Our analysis points out the mistake of comparing the stability of different monetary systems with the same indicators. The application of a VAR model enabled us to isolate the period 1854-1891 as being the one that actually corresponds to what we expect of gold standard behaviour. Examination of demand, supply and monetary shocks yields interesting results that confirm the idea that the principles of classical economics are appropriate for the gold standard period.